Taliban resurgence in Afghanistan : the role of post-conflict reconstruction - Sadia Sulaiman (2015)
The objective of this thesis is to analyze why the Taliban-led insurgency in Afghanistan emerged despite lack of support from the Afghan people on the one hand and significant external assistance on the other.